A neglected cervicovesical fistula diagnosed and repaired by combined hysteroscopy and laparoscopy: A case report and review of literature - Sun, Dongjing; Xu, Wenzhi; Chen, Yicheng; Chen, Xueyuan; Lin, Xiaona (Frontiers in Surgery, 2022)
Objective To analyze a case of neglected cervicovesical fistula with intrauterine adhesions caused by cesarean section. Methods A 36-year-old female patient with a history of two previous cesarean sections complained of the absence of menstruation for the last 18 months. The diagnosis of the cervicovesical fistula was made through hysteroscopy and cystoscopy. The reconstruction of the uterus and bladder was achieved by a laparoscopic repair technique. Results The patient resumed normal menstruation postoperatively without complaining of any complications. Uterine continuity and cavity had been restored to normal at the second look of hysteroscopy. Conclusions Cervicovesical fistula with intrauterine adhesions is very rare in our clinical work. Hysteroscopy might play an essential role in diagnosing cervicovesical fistula and IUA. In our literature review, a surgical approach was the mainstay and definitive management of the cervicovesical fistula following a cesarean section.